Consider a quadratic form "x^2-2xy+y^2" (for a differential equation "A_{11}\\frac{\\partial^2 z}{\\partial x^2}+A_{12}\\frac{\\partial^2 z}{\\partial x\\partial y}+A_{22}\\frac{\\partial^2 z}{\\partial y^2}+\\ldots=0" we consider a quadratic form "A_{11}x^2+A_{12}xy+A_{22}y^2" ). Its matrix is "\\begin{pmatrix}\n 1 & -1 \\\\\n -1 & 1\n\\end{pmatrix}" with eigenvectors "(1,1)" and "(1,-1)" .
So we have change of the variables: "u=1\\cdot x+1\\cdot y = x+y" and "v=1\\cdot x+(-1)\\cdot y = x-y" .
Then "\\frac{\\partial f}{\\partial x}=\\frac{\\partial f}{\\partial u}\\frac{\\partial u}{\\partial x}+\\frac{\\partial f}{\\partial v}\\frac{\\partial v}{\\partial x}=\\frac{\\partial f}{\\partial u}+\\frac{\\partial f}{\\partial v}" and "\\frac{\\partial f}{\\partial y}=\\frac{\\partial f}{\\partial u}\\frac{\\partial u}{\\partial y}+\\frac{\\partial f}{\\partial v}\\frac{\\partial v}{\\partial y}=\\frac{\\partial f}{\\partial u}-\\frac{\\partial f}{\\partial v}" . Move from the variables "x,y" to the variables "u,v" .
In case "f=z" we have "\\frac{\\partial z}{\\partial x}=\\frac{\\partial z}{\\partial u}+\\frac{\\partial z}{\\partial v}" and "\\frac{\\partial z}{\\partial y}=\\frac{\\partial z}{\\partial u}-\\frac{\\partial z}{\\partial v}" .
In case "f=\\frac{\\partial z}{\\partial x}" we have "\\frac{\\partial^2 z}{\\partial x^2}=\\frac{\\partial}{\\partial x}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)=\\frac{\\partial}{\\partial u}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)+\\frac{\\partial}{\\partial v}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)=\\frac{\\partial^2 z}{\\partial u^2}+2\\frac{\\partial^2 z}{\\partial u\\partial v}+\\frac{\\partial^2 z}{\\partial v^2}" and "\\frac{\\partial^2 z}{\\partial x\\partial y}=\\frac{\\partial}{\\partial y}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)=\\frac{\\partial}{\\partial u}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)-\\frac{\\partial}{\\partial v}\\bigl(\\frac{\\partial z}{\\partial x}\\bigr)=\\frac{\\partial^2 z}{\\partial u^2}-\\frac{\\partial^2 z}{\\partial v^2}"
In case "f=\\frac{\\partial z}{\\partial y}" we have "\\frac{\\partial^2 z}{\\partial y^2}=\\frac{\\partial}{\\partial y}\\bigl(\\frac{\\partial z}{\\partial y}\\bigr)=\\frac{\\partial}{\\partial u}\\bigl(\\frac{\\partial z}{\\partial y}\\bigr)-\\frac{\\partial}{\\partial v}\\bigl(\\frac{\\partial z}{\\partial y}\\bigr)=\\frac{\\partial^2 z}{\\partial u^2}-2\\frac{\\partial^2 z}{\\partial u\\partial v}+\\frac{\\partial^2 z}{\\partial v^2}" .
In addition "x=\\frac{u+v}{2}" and "y=\\frac{u-v}{2}" .
Rewrite the original equation: "\\bigl(\\frac{\\partial^2 z}{\\partial u^2}+2\\frac{\\partial^2 z}{\\partial u\\partial v}+\\frac{\\partial^2 z}{\\partial v^2}\\bigr)-2\\bigl(\\frac{\\partial^2 z}{\\partial u^2}-\\frac{\\partial^2 z}{\\partial v^2}\\bigr)+"
"+\\bigl(\\frac{\\partial^2 z}{\\partial u^2}-2\\frac{\\partial^2 z}{\\partial u\\partial v}+\\frac{\\partial^2 z}{\\partial v^2}\\bigr)=12\\frac{u+v}{2}\\frac{u-v}{2}" . That is "\\frac{\\partial^2 z}{\\partial v^2}=\\frac{3}{4}u^2-\\frac{3}{4}v^2"
Integrate it with respect to "v" : "\\frac{\\partial z}{\\partial v}=\\frac{3}{4}u^2v-\\frac{1}{4}v^3+R(u)" and again "z=\\frac{3}{8}u^2v^2-\\frac{1}{16}v^4+R(u)v+S(u)",
where "R(u), S(u)" are arbitrary twice differentiable functions.
Return to the variables "x" and "y" : "z=\\frac{3}{8}(x+y)^2(x-y)^2-\\frac{1}{16}(x-y)^4+(x-y)\\cdot R(x+y)+"
"+S(x+y)"
Comments
Leave a comment